Strategi Pemasaran Dalam Meningkatkan Minat Siswa Baru Pada SD Negeri 17 Palu - Syerina Evayanti; Ponirin Ponirin; Maskuri Sutomo; Farid Farid (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to examine in depth the marketing strategy in increasing the interest of new students at SD Negeri 17 Palu, what are the supporting and inhibiting factors for educational marketing carried out by the school principal. The type of research method used is a qualitative research method with a descriptive approach. The location used as an object by researchers is SD Negeri 17 Palu. Data collection techniques in this research are through observation, interviews and documentation. Data analysis was carried out in three stages, namely data reduction, data display, and conclusion drawing/verification. The results of interviews with school principals revealed that in marketing or promoting the school, they continued to maintain the existence of the school by prioritizing the quality of the products and services offered. However, as time went by, the quality of the school decreased due to inadequate marketing strategies, which led to a decline in the quality of the school. Interview results from school operators show that from 2022 to 2024, there will be a significant decline in the number of students enrolling at Palu 17 Public Elementary School. Data analysis shows that in 2022, the number of registrants reaches its peak, but then decreases by 15% in 2023 and 10% in 2024. Recommendations that can be given involve increasing focus on a more specific target audience, improving the quality of marketing campaigns, and strengthening collaboration with related parties, such as local communities.